Answer:
Option (D)
Step-by-step explanation:
Given equation is,
[tex]8e^{2x+1}=4[/tex]
Taking natural log on both the sides of the equation,
[tex]\text{ln}(8e^{2x+1})=\text{ln}(4)[/tex]
[tex]\text{ln}(2^3)+\text{ln}(e^{2x+1})=\text{ln}(2^2)[/tex]
3ln(2) + (2x + 1)[ln(e)] = 2ln(2)
2n(2) - 3ln(2) = (2x + 1)
2x = -ln(2) - 1
[tex]2x=\text{ln}(\frac{1}{2})-1[/tex] [Since, -ln(2) = ln(1) - ln(2) = [tex]\text{ln}(\frac{1}{2})[/tex]]
[tex]2x=\text{ln(0.5)}-1[/tex]
[tex]x=\frac{\text{ln(0.5)-1}}{2}[/tex]
Therefore, Option (D) will be the correct option.